2013
DOI: 10.1080/17429145.2012.754959
|View full text |Cite
|
Sign up to set email alerts
|

Leaf recovery responses during rehydration after water deficit in two bean (Phaseolus vulgarisL.) cultivars

Abstract: Our hypothesis was that recovery responses (RI and RII) upon rehydration, after 1 and 8 d of moderate (WDI) and severe water deficit (WDII), are evidence of tolerance in two commercial bean cultivars, Tacarigua (T cv) and VUL-73-40 (V cv). Recovery of leaf water (Cw) and osmotic potentials (Cs), and relative water content (LRWC), showed strong dependence on soil water potential (sCw) followed by protein content; recovery connection between stomatal conductance and soil Cw is showed. Chlorophyll (a 'b), Ribulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The recovery of pigments in the tolerant cultivar after rehydration is an indication that was recovered the physiological competence, after significant losses of water fraction in tissues. Trujillo et al (2013) also observed negative impacts on the pigments of two cultivars of Phaseolus vulgaris after eight days of water deficit, and it observed a slight recovery of these parameters after one day of rehydration, corroborating the results obtained in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The recovery of pigments in the tolerant cultivar after rehydration is an indication that was recovered the physiological competence, after significant losses of water fraction in tissues. Trujillo et al (2013) also observed negative impacts on the pigments of two cultivars of Phaseolus vulgaris after eight days of water deficit, and it observed a slight recovery of these parameters after one day of rehydration, corroborating the results obtained in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Reduced leaf area as response to drought is in accordance with Givnish & Vermeij () and Trujillo et al . (). For most species in our study, however, the relationship between leaf area and leaf biomass seemed to be relatively stable.…”
Section: Discussionmentioning
confidence: 97%
“…growing smaller leaves, is a typical plant response to drought of adult plants (Trujillo et al . ) and of seedlings (Koike et al . ; Wu et al .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reduction of the specific leaf area, as observed in RB72910 and RB92579 varieties, indicates a strategy of acclimatization to water stress with greater potential for maintenance of crop productivity. The reduction in specific leaf area in plants under water stress indicates higher leaf thickness, which may help to maintain water in the leaf tissue, therefore, allowing a more favorable response to drought (Lopez et al, 1997;Trujillo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Under drought stress, plants can increase leaf thickness as a mechanism to keep more leaf water content (Lopez et al, 1997;Trujillo et al, 2013). Moreover, under these conditions, plants tend to close stomatal in an attempt to restrict water loss through transpiration (Machado et al, 2009;Medeiros et al, 2013;Ribeiro et al, 2013), which also reduces the photosynthesis (Endres et al, 2010;Sales et al, 2012).…”
Section: Introductionmentioning
confidence: 99%